2014
DOI: 10.1149/06403.0371ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Development of PFSA Ionomers for the Membrane and the Electrodes

Abstract: Perfluorosulfonic acid (PFSA) ionomer is one of the key materials used in polymer electrolyte fuel cell (PEFC). Most of the membranes used in high performance and high durability PEFC are made from PFSA ionomers. The ionomer for the membrane is required to perform well at high temperatures up to 120 °C at low relative humidity (RH). The ionomer for the electrode, besides transporting the protons to the membrane, its function in cathode of delivering the oxygen to the Pt surface is highlighted in the recent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Reproduced with permission. [ 116a ] Copyright 2005, IOP Publishing. c) Chemical structures and oxygen transport mechanism of Nafion (top) and PFMMD‐co‐PFSA (bottom).…”
Section: Strategies To Reduce Rlocalmentioning
confidence: 99%
“…Reproduced with permission. [ 116a ] Copyright 2005, IOP Publishing. c) Chemical structures and oxygen transport mechanism of Nafion (top) and PFMMD‐co‐PFSA (bottom).…”
Section: Strategies To Reduce Rlocalmentioning
confidence: 99%
“…The most significant impact observed is when a small cyclical ring is inserted into the ionomer backbone in order to create a sterically enhanced O 2 permeability through a more open structure (Fig. 9) [100][101][102]. This results in a substantial improvement in HCD voltage as shown in Fig.…”
Section: Ionomer Thin Film and Ionomer-pt Interfacementioning
confidence: 99%
“…Attempts to improve O 2 permeability through a more open structure ionomer are also being pursued with encouraging results. A basic strategy is to insert a small cyclical ring into the backbone to create a sterically enhanced O 2 permeability (Figure b). It was shown that this strategy could increase O 2 permeability by a factor of 2–20 in a bulk membrane.…”
mentioning
confidence: 99%